Functional characterization of graphene-based thin-film microelectrodes on rat sensorimotor cortex - Duvan, Fikret Taygun. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2020., 2020)
Neuroprostheses based on cortical implants are promising to provide partial sensorimotor function in severe neurological conditions such as spinal cord injuries and amyotrophic lateral sclerosis. One of the key components of these systems is the microelectrode array, which is used for recording brain activity to control a robotic limb and/or for stimulation to induce somatosensory feedback. Graphene is a good candidate as electrode material due to its intrinsic features such as high electrical conductivity and charge injection capacity, high mechanical strength, flexibility and biocompatibility. Evoked local field potentials were recorded epidurally at the hindpaw representation of SI in anesthetized Wistar albino rats. The vibrotactile stimuli were bursts of sinusoidal (5-, 40-, and 250-Hz) displacements (duration: 0.5-s, amplitude range: 19 - 270 m) applied on the glabrous skin. Performance comparisons were made between matching research grade graphene and commercial Pt-Ir surface electrodes on the same subjects (active site diameter: 25- m). Robust evoked potentials could be observed shortly after the onset of contralateral stimuli in both electrodes. Pt- Ir electrodes exhibited slightly higher SNR while the lowest impedances were recorded from the channels of the graphene array. Variance of the impedance values were smaller for the channels of the Pt-Ir electrodes. The performance of the graphene electrode channels was observed to be heterogeneous due to ongoing development efforts. This thesis includes one of the first functional tests of graphene electrodes during processing of the natural sensory stimuli in the brain.|Keywords : Primary somatosensory cortex, Cortical recording, Electrical stimulation of the brain, Surface electrodes, Local field potentials.
Keywords: Neuroprostheses -- Design and construction.; Graphene.; Brain stimulation.; Electric stimulation.